Comparative Analysis of Methane Emission from Energy Sources in Azerbaijan, Kazakhstan, and Russia - Yusifli, Elshan (ADA University, 2023)
Methane is an important greenhouse gas standing as a potential threat to climate by contributing to global warming. Numerous studies conclude that in terms of its warming potential, methane is 86 times more powerful than carbon-dioxide although its lifespan in the atmosphere is much shorter than CO2. It is reported that methane concentration in the atmosphere has increased more than 2.5 times compared to the figures of pre industrial periods and 30% of the rise in global temperature is attributed to methane leakage related activities. However, increasing concentration of greenhouse gas in the atmosphere has not received sufficient attention from the global community excluding recently accepted conventions and agreements. In this study, methane emission from energy sources is comparatively analyzed in the example of Azerbaijan, Kazakhstan, and Russia. Based on both primary and secondary data, emission sources are identified. By employing Multiple Linear Regression analysis, effects of 4 explanatory variables on methane emission from energy sources are tested. Regression results indicate that in Azerbaijan, total oil and natural gas production, coal consumption, and natural gas flaring positively contributes to methane emission while hydroelectricity generation demonstrated no significant effect. On the other hand, total oil and natural gas production, coal consumption, and hydroelectricity generation indicate positive effect on CH4 emission for Kazakhstan whereas no significant effect of natural gas flaring is found. Finally, regression analysis concludes that all three tested variables have positive effect on methane emission from energy sector in Russia; however, the effect of natural gas flaring could not be tested since official data is not available for Russia. Additionally, the study also presents various mitigation techniques regarding the emission of greenhouse gas.
Keywords: Methane -- Environmental aspects; Greenhouse gases -- Emission control; Energy industries -- Environmental aspects -- Azerbaijan, Kazakhstan, Russia; Public and International Affairs